2017
DOI: 10.1002/slct.201700556
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Synthesis of CuFe2O4@rGO: Efficient Catalyst for C‐O Cross Coupling and N‐arylation Reaction under Ligand‐Free Condition

Abstract: In this paper, we report copper ferrite supported reduced graphene oxide (CuFe2O4@rGO) synthesis by solvothermal process. The prepared CuFe2O4@rGO catalyst was used for C‐O and C‐N cross coupling reactions. The activity of the catalyst was compared with commercial Cu2O, CuOand CuFe2O4 for C‐O cross coupling of iodobenzene with phenol. CuFe2O4@rGO was the best catalyst with 97% conversion towards iodobenzene at 100°C under ligand free condition which is otherwise normally used. The virgin and five times reused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…The optimization showed that the best agitation rate 600 rpm and only 1 × 10 −3 g/cm 3 of CuFe 2 O 4 @RGO catalyst is needed to obtain the highest yield of the products (Scheme 19). The kinetic study of the C-O bond formation was the second-order rate of reaction where the activation energy was observed to be 14.36 kcal/mol, and the catalyst could be reused up to five times without losing its catalytic activity ( Figure 8) [57].…”
Section: Scheme 14 Maghemite-copper Oxide Nanoparticles Catalyzed Symentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization showed that the best agitation rate 600 rpm and only 1 × 10 −3 g/cm 3 of CuFe 2 O 4 @RGO catalyst is needed to obtain the highest yield of the products (Scheme 19). The kinetic study of the C-O bond formation was the second-order rate of reaction where the activation energy was observed to be 14.36 kcal/mol, and the catalyst could be reused up to five times without losing its catalytic activity ( Figure 8) [57].…”
Section: Scheme 14 Maghemite-copper Oxide Nanoparticles Catalyzed Symentioning
confidence: 99%
“…Catalysts 2020, 10, x FOR PEER REVIEW 15 of 51 rpm and only 1 × 10 −3 g/cm 3 of CuFe2O4@RGO catalyst is needed to obtain the highest yield of the products (Scheme 19). The kinetic study of the C-O bond formation was the second-order rate of reaction where the activation energy was observed to be 14.36 kcal/mol, and the catalyst could be reused up to five times without losing its catalytic activity ( Figure 8) [57]. In a continuous study on the preparation of new recoverable magnetic nanoparticles, Iman Radfar et al proposed a new magnetic nanoparticle functionalized sugar onto the silicon dioxide solid (Scheme 20).…”
Section: Scheme 14 Maghemite-copper Oxide Nanoparticles Catalyzed Symentioning
confidence: 99%
“…Each Fe 2p lines can be deconvolved into two peaks, as shown in Figure S1A. The doublets of Fe 2p 3/2 binding energy at 710.4 eV and Fe 2p 1/2 binding energy at 723.7 eV are assigned to the Fe 3+ ions in octahedral sites, while the doublets of Fe 2p 3/2 binding energy at 712.8 eV and Fe 2p 1/2 binding energy at 725.7 eV are assigned to Fe 3+ ions in tetrahedral sites [26]. Moreover, the relative contributions to the overall intensity of Fe 3+ ions at the octahedral and tetrahedral sites are 40% and 60%, calculated from the ratio of peak area.…”
Section: Morphology and Structurementioning
confidence: 99%
“…50–52 However, such systems have been rarely used for C–O bond forming reactions for the formation of diaryl ethers. 3,6,53–56…”
Section: Introductionmentioning
confidence: 99%